Crossing the curriculum : multilingual learners in college classrooms - Zamel, Vivian; Spack, Ruth (L. Erlbaum Associates, 2004)
This text examines multilingual learners in college classrooms and covers subjects including: experiences of ESOL students and faculty across the curriculum; acquiring academic literacy in a second language; and helping students use writing to learn.